2022
DOI: 10.3390/d14070570
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Plants around the Cross-Border Area of Greece and the Republic of North Macedonia: Integrated Conservation Actions and Sustainable Exploitation Potential

Abstract: Plants know no political borders and some of them are restricted to small geographical territories of different countries in which they are endemic. In this study, we prioritized plants (PPs) of the cross-border area of Greece and the Republic of North Macedonia that are already threatened or nearly so (PPA), those which occur exclusively on either side of borderline and/or nearby countries (PPB), or those which are uncommon and rare in this region (PPC) with the aim to document in-situ the species-specific ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Furthermore, conservation efforts have been increased to date to achieve effective protection for local endemic NUPs, especially for those threatened with extinction [2]. Significant information on both the economic and biological value of threatened local endemic NUPs has been gathered through species-specific studies [2,[11][12][13], and basic research gaps related to their propagation and ex-situ cultivation protocols have been addressed during the last decade [2,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, conservation efforts have been increased to date to achieve effective protection for local endemic NUPs, especially for those threatened with extinction [2]. Significant information on both the economic and biological value of threatened local endemic NUPs has been gathered through species-specific studies [2,[11][12][13], and basic research gaps related to their propagation and ex-situ cultivation protocols have been addressed during the last decade [2,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, this has also been often coupled by potential economic benefits associated with their sustainable utilization and concomitant exploitation [2,11,12]. The effectiveness of these two research directions can be facilitated by information on the environmental conditions associated with targeted NUPs reflecting their adaptation in natural habitats and their ecological preferences [2,[15][16][17][18][19][20][22][23][24][25][26]28]. Such data can be utilized to adjust or improve their propagation conditions, for example, through seed propagation [30], which is the most economical and efficient propagation method for many plant species [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as shown above, species protection catalogs also differ between communities. However, plants recognize no political boundaries, and some are confined to specific geographic regions within different countries, making conservation management necessitate a comprehensive strategy [88].…”
Section: Discussionmentioning
confidence: 99%
“…The endemicity criterion is intrinsically linked to the concept of responsibility [85][86][87][88]; that is, if a species is confined to a specific geographic territory, it is the obligation of the respective governing authorities within that territory to establish a protection regime, as they are responsible for its monitoring and conservation. The smaller the territory, the higher the level of government responsibility for its protection, particularly when all the taxa are threatened and/or protected, as is the case in this study.…”
Section: Endemicitymentioning
confidence: 99%
“…It is important to note that native species within the genus are subject to protective measures and local conservation initiatives (van de Kasteele, 1974;Krigas et al, 2022). In Greece, local populations of L. chalcedonicum such as those located in Parnitha National Park face significant pressures and threats (Aplada et al, 2007), while they can be found in other protected areas (Mertzanis et al, 2016).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%